Understanding and Supporting for Village SDG 8 (Equitable Economic Growth): Strategies Toward Sustainable Rural Development - Sofie, Sofie; Handoyo, Rahmat; Gunawan, Juniati; Liu, Ying Chieh; Anthonius, Anthonius (Indonesian Journal of Sustainability Accounting and Management, 2025)
This research aimed to assess the understanding and support of micro-entrepreneurs, village officials, and private sector stakeholders regarding the implementation of Village SDG Goal 8. A qualitative and exploratory approach was employed, utilizing questionnaires, Focus Group Discussions (FGDs), in-depth interviews, and field observations as data collection techniques. The analysis was based on 17 indicators of Village SDG Goal 8, and the study was grounded in Legitimacy Theory. The units of analysis consisted of micro-entrepreneurs, village officials, and private sector stakeholders. The findings indicated that levels of understanding and support varied across the three stakeholder groups. Micro- entrepreneurs generally demonstrated lower awareness and commitment compared to village officials and private stakeholders. These variations underscored the need for targeted strategies to enhance stakeholder engagement in achieving the indicators of Village SDG Goal 8. This study contributes to the formulation of action plans aimed at increasing stakeholder understanding and support for Village SDG indicators. Furthermore, the findings can provide valuable input for The Ministry of National Development Planning and the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration in designing policies related to village fund allocations that are aligned with Village SDG targets.